The Effect of Job Satisfaction and Self Efficacy on Turnover Intention among Generation Z Employees in Sidoarjo - Hamidaya, Novita Sari; Iryanti, Endang; Rosyanti, Daisy Marthina (PT Larva Wijaya Penerbit, 2025)
Turnover intention is defined as employees’ tendency to leave the organization, either through the desire to seek new employment or by planning to resign. This phenomenon has become an important issue in human resource management, particularly among Generation Z employees who are known to have relatively high job mobility. The research was conducted to investigate the relationship between job satisfaction, self efficacy, and turnover intention. Employing a quantitative framework, 120 Generation Z respondents from Sidoarjo were surveyed through questionnaires,and the results were analyzed using PLS-SEM with SmartPLS software. The study results indicate that job satisfaction significantly reduces turnover intention. Likewise, self efficacy was proven to have a significant negative impact on turnover intention. In other words, employees with higher job satisfaction and stronger self efficacy are less likely to develop the intention to leave their organization.